Assessment of malaria reporting and epidemic preparedness systems in health facilities in Eldoret West District, Uasin Gishu County, Kenya - Ruth C. Kirinyet; Arthur S. Ng'etich; Ahmad Juma (AOSIS, 2016)
The most important factor in reducing the impact of an epidemic is a timely response with implementation of effective control measures at the point of detection. This study sought to assess the malaria reporting and epidemic preparedness systems of health facilities in Eldoret West District, Kenya. A crosssectional study design was adapted. A census technique was used to select all the forty five health facilities in the district comprising of government, mission and non-governmental facilities. An interviewer administered questionnaire was used for data collection and analysis done using Stata. Categorical variables were summarized as frequencies and corresponding percentages. The overall reporting rate was 91.7% for all the health facilities. Only 15 health facilities (33%) plotted malaria trend lines for number of cases of malaria. Malaria epidemics were reported within 24 hours in 22 health facilities but they lacked the appropriate supplies to respond to confirmed cases or epidemics. The overall malaria reporting completeness rate was above 90% implying that the malaria surveillance system was generally good. Concerted efforts by concerned stakeholders should ensure improvement of malaria epidemic preparedness system in all health facilities and provision of information to health personnel on malaria outbreak response strategies.